Platinum-Based Neoadjuvant Chemotherapy for Breast Cancer With BRCA Mutations: A Meta-Analysis - Wang, Chang-Jun; Xu, Ying; Lin, Yan; Zhu, Han-Jiang; Zhou, Yi-Dong; Mao, Feng; Zhang, Xiao-Hui; Huang, Xin; Zhong, Ying; Sun, Qiang; Li, Cheng-Gang (Frontiers in Oncology, 2020)
Background: Triple-negative breast cancer (TNBC) is one of the most aggressive subtypes of breast cancer and the major phenotype of BRCA related hereditary breast cancer. Platinum is a promising chemotherapeutic agent for TNBC. However, its efficacy for breast cancer with BRCA germline mutation remains inconclusive. Here we present a meta-analysis to evaluate the effect of platinum agents for breast cancer patients with BRCA mutation in neoadjuvant setting. Materials and Methods: Pubmed, Embase and Cochrane Central Register of Controlled Trials databases were searched for relevant studies on neoadjuvant platinum treatment and BRCA related breast cancer. Fixed- and random-effect models were adopted for meta-analyses. Heterogeneity investigation was conducted by sensitivity and subgroup analyses. Publication bias was evaluated by funnel plot and Begg’s test. Results: In all, five studies with 363 patients were included for meta-analysis. The pooled pathological complete response (pCR) rates were 43.4% (59/136) and 33.9% (77/227) for platinum and control groups, respectively. Adding platinum to neoadjuvant regimen did not significantly improved pCR rate (odds ratio [OR] 1.340, 95% confidence interval [CI] = 0.677 – 2.653, p = 0.400). Sensitivity analyses also revealed platinum did not significantly increase pCR rate in either TNBC or HER2- patients (TNBC subgroup: OR 1.028, 95% CI = 0.779 – 1.356, p = 0.846; HER2- subgroup: OR 0.935, 95% CI = 0.716 – 1.221, p = 0.622). Conclusions: Our meta-analysis suggested that the addition of platinum to neoadjuvant chemotherapy did not significantly improve pCR rate for patients with BRCA mutations. Further large-scale randomized control trial with survival data may provide more robust evidence on therapeutic value of platinum for breast cancer neoadjuvant treatment.